1985
DOI: 10.1039/c39850001275
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated ion transport in a biomembrane model. Artificial ion channels as pores in dihexadecyl phosphate vesicles

Abstract: An artificial ion channel, composed of stacks of crown ether rings, forms a pore in bilayers of dihexadecyl phosphate vesicles and facilitates the transmembranous transport of cobalt ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12] Some successful approach gave compounds that showed single-channel activity. [13][14][15][16][17][18][19][20][21][22][23][24][25] In our laboratory, we have described a general strategy to prepare supramolecular devices having a predictable structure 26 using polypeptides as frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Some successful approach gave compounds that showed single-channel activity. [13][14][15][16][17][18][19][20][21][22][23][24][25] In our laboratory, we have described a general strategy to prepare supramolecular devices having a predictable structure 26 using polypeptides as frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…2 was synthesized from 4'-(2-carboxyvinyl) benzo-15-crown-5 '') as described below. 4'-(2-carboxyvinyl)benzo-l5-crown-5 (4,O g; 12 mmol) was reduced at room temperature by hydrogen in a mixed solvent of ethanol (200 mL) and acetic acid (100 mL) in the presence of Pd/C (3,O 9). After filtration, the filtrate was concentrated in vacuo.…”
Section: Experimental Partmentioning
confidence: 99%
“…For highly sensitive and selective interactions, crown ether has a great advantage in comparison with other binding groups because crown ether allows ideal design toward targeted guest molecules, promising a guest‐specific binding ability 18, 19. Therefore, rapidly increasing attention has been paid to the synthesis and characterization of helical polymers with crown ether 20–26. Roks and Nolte22 revealed that polyisocyanide bearing crown ether, in which the crown ether rings were cofacially stacked on the basis of the rigid 4 1 helical structure, acted as an ion channel.…”
Section: Introductionmentioning
confidence: 99%